Assimilation of Voiced Plosive /d/ in Word-final Position in Ossetian Language - V. T. Dzakhova (Научный диалог)
This study investigates consonant clusters in modern Ossetian (Iron dialect). The primary aim is to establish the phonetic characteristics and phonological status of sounds produced by native speakers in place of orthographic voiced consonants. The research material comprises Ossetian words containing consonant clusters. Native speakers of Ossetian, with no deviations from normative pronunciation, served as the sources for digital recordings of the words. The methods employed in this study include instrumental analysis (oscillogram analysis) and statistical techniques. The novelty of this research lies in its focus on combinatory changes of Ossetian consonants, a topic that has not been previously addressed in the scientific discourse. The relevance of this study is underscored by the necessity for the data obtained to contribute to the development of an orthoepic dictionary of the Ossetian language. The following conclusions can be drawn: (1) In the position of orthographic voiced plosive consonants at word-end, voiceless counterparts are realized, regardless of the quality of the preceding consonant; (2) The phonemic status of the consonant realized in final position should be classified as voiceless plosive.